Efficient charge-transport UV sensor based on interlinked ZnO tetrapod networks - Meechai Thepnurat (2018)
© 2016 Elsevier B.V. UV sensors based on inter-linked ZnO tetrapod networks (ITN-ZnO) were fabricated, characterized and compared with ones based on ZnO tetrapods (T-ZnO) and ZnO powders (P-ZnO) in terms of morphology-related charge dynamics. Photoluminescence measurement showed that the ITN-ZnO had the highest order of crystallinity among these nanostructures. Moreover, impedance spectroscopy analysis revealed that potential barrier at the grain boundary of ITN-ZnO was relatively lower that of T-ZnO and P-ZnO. This was because the coulombic leg-to-leg linking of ITN-ZnO as confirmed by electron microscope observation. The lower potential barriers significantly promoted transport of UV-generated charge carriers that were required to reach Au electrodes, leading to lower sensor resistance. Based on the achieved results, charge transport mechanisms were also proposed. These sensor characteristics suggested that the ITN-ZnO was greatly applicable for UV sensors and other optoelectronic devices.